Europe's unknown war. (July 2017) - Webber, Frances
The EU's response to the global 'refugee crisis' has involved the returning of refugees to war zones, for example in Afghanistan, in breach of human rights conventions. But it has also been so determined to stop further asylum seekers reaching European waters or shores that it has entered into the most dubious of agreements with countries outside the EU. Using bribery (aid, promises of investment, even the prospect of membership of the EU) and blackmail (threats of withdrawal of support for educational and health programmes), the EU has inveigled and browbeaten countries around the Mediterranean and as far afield as sub-Saharan Africa, to undertake immigration controls on its behalf. This has involved the EU in agreements with repressive regimes such as Turkey, Sudan and Eritrea, designed to block the movements of millions of people in the Middle East and Africa necessitated by war, famine, climate change and religious conflict. The outsourcing of migration policy to countries run by known dictators and war criminals has come at the expense of Europe's humanitarian tradition, argues the author, who looks at the implications of policy by country and region.